2018
DOI: 10.1111/ans.14297
|View full text |Cite
|
Sign up to set email alerts
|

Increasing success in outpatient laparoscopic cholecystectomy by an optimal clinical pathway

Abstract: Optimal clinical pathway (more convincing and reassuring remarks in the preoperative consult and a dedicated outpatient facility) is the key to increase success in outpatient laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Implementation of a dedicated care pathway for patients undergoing elective LC was examined in 10 non-randomized studies. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 14 , 31 , 32 Implementation of a care pathway was associated with a significantly shorter mean LOS (MD 24.9 h; 95% CI, 18.7–31.2; p < 0.001; Fig. 3 a) and an improved day case rate (OR, 3.5; 95% CI, 1.5–8.1; p = 0.005; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of a dedicated care pathway for patients undergoing elective LC was examined in 10 non-randomized studies. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 14 , 31 , 32 Implementation of a care pathway was associated with a significantly shorter mean LOS (MD 24.9 h; 95% CI, 18.7–31.2; p < 0.001; Fig. 3 a) and an improved day case rate (OR, 3.5; 95% CI, 1.5–8.1; p = 0.005; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 , 3 , 4 , 5 Implementation of standard clinical pathways for LC have been reported to successfully reduce LOS and increase day case success. 6 , 7 , 8 , 9 , 10 , 11 , 12 Day case laparoscopic cholecystectomy (DCLC) is associated with cost-savings 3 , 13 , 14 without increasing the risk of adverse events or readmissions. 3 , 15 , 16 It has a high rate of patient satisfaction 17 , 18 and is comparable with inpatient stay with respect to quality of life, return to work and normal activity.…”
Section: Introductionmentioning
confidence: 99%
“…The strict use of an effective postoperative scoring system could be one method implemented at YG and LLGH to increase the proportion of successful DCLCs. The 'Chung Score' suggested by Greilsamer et al (2018) is a post-anaesthetic discharge criteria that evaluates patients' fitness following day-case surgery (Daradkeh et al 1998). Its use has shown to significantly increase the success of outpatient DCLCs by providing a clear, succinct pathway towards safe and appropriate discharge (Greilsamer et al 2018, Randhawa & Pujahari 2009.The current surgical day-case wards at YG and LLGH follow a discharge criterion with some similarities to the Chung Score (such as postoperative mobility, nausea/vomiting and pain).…”
Section: Further Workmentioning
confidence: 99%
“…As LC is one of the first procedures performed by surgical trainees (Greilsamer et al 2018), surgeon experience for the failed DCLCs at YG and LLGH may provide insight and reasoning behind intra/ postoperative complications, conversions to open LC and readmissions seen. Although operation times are longer in LCs performed by trainees compared to consultant level surgeons, Atta et al suggests no differences in complication rates when trainees are observed by their seniors (Atta et al 2017, Greilsamer et al 2018. Investigation into LC operation waiting times after acute cholecystitis presentation or following ERCP would also benefit practice by creating an optimum time frame for these patients selected for LC surgery at LLGH isolated day unit.…”
Section: Further Workmentioning
confidence: 99%
“…6,7 For example in laparoscopic cholecystectomy, this even led to successful twenty-four hours discharge for 96% of patients and reduced length of stay for this entire patient population. [8][9][10][11][12][13] This was cost-effective and increased bed capacity without increased readmission rates. 9,12,14 These benefits are important considering the increasing healthcare costs worldwide.…”
Section: Introductionmentioning
confidence: 99%